Portugal: Leapfrogging Digital Transformation - Estevez, Elsa Clara (2021)
This report is structured as follow: Section 1 presents details about Portugal enabling or inhibiting its digital transformation. Section 2 analyzes the main motivations for the digital transformation strategy; Section 3 summarizes its main challenges, while Section 4 presents the main components of the strategy. Section 5 analyzes the governance model, and Section 6, the legal and regulatory framework. Section 7 discusses critical enablers for the digital transformation of government services. Section 8 introduces 16 key initiatives of the strategy. Section 9 summarizes the lessons learnt, followed by an assessment of the strategy’s impact in Section 10. Section 11 synthesizes lessons for Latin American countries. Finally, Appendix A enumerates main legal and regulatory instruments supporting the digital transformation in Portugal, Appendix B presents a set of 18 sections providing details of the initiatives analyzed in the report1, and Appendix C explains how the digital transformation efforts contributed to face the challenges raised by the COVID-19 pandemics.